Market Oriented Product Innovation : A Key to Survival in the Third Millennium - Holt, Knut (Springer US, 2002)
Market-Oriented Product Innovation differs from most other titles, written either from a marketing or technical perspective, by giving a holistic view of the product innovation process. It has a product perspective, written from a managerial point of view, recognizing that product innovation, or new product development, is a discipline of its own. It is concerned with managing the products (goods and services) through their life cycle, integrating marketing knowledge and technological expertise, with the aim of getting satisfied customers. The book also gives a thorough treatment of the human and cultural aspects of product innovation by focusing on the change processes needed for the development of a market-oriented culture.